Multi-instrument observations of the solar eclipse on 20 March 2015 and its effects on the ionosphere over Belgium and Europe - Stankov, Stanimir; Bergeot, Nicolas; Berghmans, David; Bolsée, David; Pierrard, Viviane (Journal of Space Weather and Space Climate, 2017)
A total solar eclipse occurred on 20 March 2015, with a totality path passing mostly above the North Atlantic Ocean, which resulted in a partial solar eclipse over Belgium and large parts of Europe. In anticipation of this event, a dedicated observational campaign was set up at the Belgian Solar-Terrestrial Centre of Excellence (STCE). The objective was to perform high-quality observations of the eclipse and the associated effects on the geospace environment by utilising the advanced space- and ground-based instrumentation available to the STCE in order to further our understanding of these effects, particularly on the ionosphere. The study highlights the crucial importance of taking into account the eclipse geometry when analysing the ionospheric behaviour during eclipses and interpreting the eclipse effects. A detailed review of the eclipse geometry proves that considering the actual obscuration level and solar zenith angle at ionospheric heights is much more important for the analysis than at the commonly referenced Earth’s surface or at the plasmaspheric heights. The eclipse occurred during the recovery phase of a strong geomagnetic storm which certainly had an impact on (some of) the ionospheric characteristics and perhaps caused the omission of some ‘‘low-profile’’ effects. However, the analysis of the ionosonde measurements, carried out at unprecedented high rates during the eclipse, suggests the occurrence of travelling ionospheric disturbances (TIDs). Also, the high temporal and spatial resolution measurements proved very important in revealing and estimating some finer details of the delay in the ionospheric reaction and the ionospheric disturbances.